Síntese e caracterização do composto TiO2 dopado com nitrogênio e estudo de sua atividade fotocatalítica sob luz visível e irradiação solar - Paz, Diego Silva (2012)
In this work was carried out the catalyst synthesis TiO2 doped with nitrogen by sol-gel method, followed by calcination step. Were used three different calcination temperatures, 400, 450 and 500 ° C, while the other synthesis parameters were kept. The compounds were characterized by X-ray diffraction spectroscopy, UV-visible region and the nitrogen adsorption BET method. The study results presented obtaining nanopowders of titanium dioxide doped with nitrogen in the anatase phase, without the presence of rutile phase with surface areas ranging between 12.94 to 151.33 m2.g-1 with crystallite sizes in the nanometer range. Adsorption studies were carried out in advance to the tests photocatalytic irradiation of visible light and sunlight. The dye used as a model for the tests was the azo dye Direct Black 38. Through the preparation of solutions with different initial concentrations of dye and using a fixed volume of solution and adsorbent concentration for the adsorption tests were determined certain parameters of the process and thermodynamic equilibrium. Thermodynamic parameters, it was observed that the adsorption process is endothermic, with characteristics of physics adsorption due to the low value of the ΔH° obtained (10.02 kJ.mol-1). Positive values of the ΔG° show that the enthalpic contribution is greater than the entropy. The parameters initial concentration of dye, catalyst concentration and pH were measured in the tests photocatalytic irradiation of visible light and sunlight. The results showed that the parameters studied, the initial concentration of dye have significant influence on the photocatalytic process, followed by pH, and finally, with less influence, the catalyst concentration. A study of the influence of annual climate stations in the photocatalytic degradation under solar irradiation is presented. The results of this study showed that the seasons have a strong influence on the results of photodegradation due to the large variation of intensity of UVB radiation between stations